Aplikasi Pengamanan Data Menggunakan Kriptografi Dengan Metode Wake dan Algoritma Des Bebasis Java Desktop - Benny Suparman; Sewaka (CV. Multi Kreasi Media, 2022)
PT. SEIV INDONESIA is a company engaged in the production of paint, this company has many productions whose data is stored in a file called the Daily Report of the Cat Production Weighing Section. This data is important data related to warehouse stock data. The problem is that this data is only stored in a folder containing files that do not have high security, so it is possible that it can be changed by irresponsible parties, causing problems that cause production results to be not the same as warehouse stock data, so software is needed to secure the data.